Feasibility study for catalytic cracking of waste plastic to produce fuel oil with reference to Malaysia and simulation using ASPEN Plus. Issue 1 (10th January 2013) - Sahu, J.N.; Mahalik, K.K.; Nam, Ho Kim; Ling, Tan Yee; Woon, Teoh Swee; bin, Muhammad Shahimi; Mohanty, Y.K.; Jayakumar, N.S.; Jamuar, S.S.
<x xml:space="preserve">Abstract</x> A technical and feasibility assessment has been conducted for catalytic cracking of waste plastics to produce fuel oils in Malaysia. The availability and current technologies for using plastic waste has been reviewed. Flow sheet for the process has been conceptualized and the material and energy balances for the process along with a plant‐wide simulation using the software ASPEN Plus have been undertaken. Amorphous silica‐alumina has been proposed as catalyst to give 94.36% conversion. Furthermore, the economic analyses for small, medium, and large scale have been done and in all cases, the rates of return (ROR) analysis have been undertaken. From the economic analysis, it has been observed that the total estimated cost for a large scale plant would be USD 58, 591, 260 for an annual feed rate of 120, 000 ton. Based on current market of gasoline and diesel the payback period for the large scale plant would be 1.42 yr with the total annual profit of USD 72, 933, 156, which corresponds to a ROR of 35.97%. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 298–307, 2014